1987
DOI: 10.1111/j.1600-0447.1987.tb02806.x
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia:

Abstract: Twenty persons with schizophrenia were identified in a community sample of 2144 adult household residents interviewed by trained lay interviewers using the Diagnostic Interview Schedule. The hierarchy-free lifetime prevalence for a variety of psychiatric disorders is compared in those with and without schizophrenia. Those with schizophrenia were found to have increased chances of having other disorders, all except one having had at least one other disorder. Major depressive episodes, obsessive compulsive disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(7 citation statements)
references
References 36 publications
0
6
1
Order By: Relevance
“…However, the magnitude of depression in the current study is lower than the reported magnitude in the USA 50% [27], China 54.6% [5], and in Poland 61% [8]. Contrarily the current prevalence is lower than the estimated magnitude of depression in Canada which was 7.3% [9]. Several factors contributed to these wide number of variations in the magnitude of depression among schizophrenic patients across the studies, including: (1) the variations in the instruments used measure depression with different psychometric properties across the studies (i.e.…”
Section: Discussioncontrasting
confidence: 67%
“…However, the magnitude of depression in the current study is lower than the reported magnitude in the USA 50% [27], China 54.6% [5], and in Poland 61% [8]. Contrarily the current prevalence is lower than the estimated magnitude of depression in Canada which was 7.3% [9]. Several factors contributed to these wide number of variations in the magnitude of depression among schizophrenic patients across the studies, including: (1) the variations in the instruments used measure depression with different psychometric properties across the studies (i.e.…”
Section: Discussioncontrasting
confidence: 67%
“…Recent studies reported that approximately 8–26% of schizophrenic patients met the DSM-IV criteria for OCD (Eisen et al, 1997; Porto et al, 1997; Poyurovsky et al, 1999, 2001; Bermanzohn et al, 2000; Tibbo et al, 2000; de Haan et al, 2002; Nechmad et al, 2003; Ohta et al, 2003; Byerly et al, 2005). However, other investigators have reported rates up to 59.2% (Bland et al, 1987). A common bias in these estimates of comorbidity lies in the enrollment of patients with OCS and not strictly OCD.…”
Section: Methodsmentioning
confidence: 91%
“…However, the two conditions appear to co-occur more commonly than their lifetime prevalence rates of 1–1.5% and 2–3%, respectively, suggest. Finally, several studies investigating OCD comorbidity reported that 10–60% of schizophrenic patients have OCS (Fenton and McGlashan, 1986; Bland et al, 1987; Berman et al, 1995a, 1998; Lysaker et al, 2000; Okasha et al, 2000; Fabisch et al, 2001; Kayahan et al, 2005). …”
Section: Methodsmentioning
confidence: 99%
“…[12] Considering the separate lifetime prevalence rates of the two illnesses [(1%–1.5% for schizophrenia[3] and 2%–3% for obsessive-compulsive disorder (OCD)[4]], it seems that obsessive-compulsive (OC) symptoms and schizophrenia coexist more often than chance. [5]…”
Section: Introductionmentioning
confidence: 99%